Motivation, culture and creativity key elements to generate entrepreneurship in higher education institutions. - Huilcapi Masacon, Magdalena Rosario; Mazacón Gómez, Martha; Caicedo Hinojosa, Luis (Revista Universidad de Guayaquil, 2021)
This work focuses on the review of the scientific basis of the organizational culture, creativity and management considered components of essential importance for the generation of enterprises and that facilitate the improvement of economic results forsmall, medium and large entrepreneurs. Culture is a fundamental component of the process of socialization and knowledge and is required to achieve advantages that allow it to compete. Its objective is to describe some approaches about culture, creativity and management for the generation ofentrepreneurship, for this a descriptive methodology was applied, which allowed ... to make observations through an observation sheet in which the results presented in the matrix were made of the entrepreneurship fair, reaching the conclusions that training and support for entrepreneurs, generates confidence to start with family businesses, thus
Keywords: Culture; Creativity; Learning; Management; Motivation